2010
DOI: 10.1039/b922657e
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium complexes derived from tridentate thioetherbis(phenolate) ligands and their activity in Diels–Alder catalysis

Abstract: Organoaluminium(III) thioetherbis(phenolate) complexes derived from 2,2-thiobis(4,6-diterbuthylphenolate) (Stdiol) and 2,2-thiobis(4,6-dimethylphenolate) (Smdiol) were prepared by reaction of AlMe3 with the diol proligands LH2 (SmdiolH2, StdiolH2). Monomeric complexes of general formulae [LAlR(L)] (L = Stdiol, R = Me, L = THF (1); L = Stdiol, R = Me, L = Et2O (2); L = Stdiol, R = iBu, L = THF) (3); L = Smdiol, R = Me, L = THF (4); L = Smdiol, R = iBu, L = THF (5)) and [LAlCl(THF)] (L = Stdiol (6); L = Smdiol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In each of the independent molecules the longest Al–O bond is to the bridging ligand ether (Al(1)–O(14) = 1.9700(19); Al(2)–O(24) = 2.128(2)), consistent with this being the most labile of the ligand oxygens. Finally, the latter bond is substantially longer than dative Al–O distances in comparable molecules. , These data are consistent with the proposed hemilability of the ligand ether and VT-NMR data showing multiple stable conformers for 1 at 26 °C that average to trigonal bipyramidal at 80 °C (Supporting Information).…”
Section: Results and Discussionsupporting
confidence: 80%
“…In each of the independent molecules the longest Al–O bond is to the bridging ligand ether (Al(1)–O(14) = 1.9700(19); Al(2)–O(24) = 2.128(2)), consistent with this being the most labile of the ligand oxygens. Finally, the latter bond is substantially longer than dative Al–O distances in comparable molecules. , These data are consistent with the proposed hemilability of the ligand ether and VT-NMR data showing multiple stable conformers for 1 at 26 °C that average to trigonal bipyramidal at 80 °C (Supporting Information).…”
Section: Results and Discussionsupporting
confidence: 80%
“…It has been shown that in the absence of donor atoms in the ortho position, the diaryl sulfide acts as monodentate with only sulfur coordinating with the metal center [3]. In the presence of donor groups (hydroxyl, thiol, imines, amides) at the ortho position, diaryl sulfides are known to coordinate with metals such as aluminum [4], palladium [5], nickel [6], platinum [7], ruthenium [8], iron [9], lanthanide [10], germanium [11] and zinc complexes [12] in a tridentate manner, whereby the sulfur is involved in coordination or bidentate binding with no sulfur coordination. Diaryl sulfides containing dicarboxylate as a donor group have not been subjected to detailed study.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic activity of the Al organyl complexes can be raised by introduction of thioether functionality. Muñoz‐Hernández et al . have prepared Organoaluminum (III) thioetherbis(phenolate) complexes derived from 2,2′‐thiobis(4,6‐diterbuthylphenolate) (Stdiol) and 2,2′‐thiobis(4,6‐dimethylphenolate) (Smdiol) by reacting AlMe 3 with the diolproligands (SmdiolH2, StdiolH2) ( Scheme ) .…”
Section: Cycloaddition Reactions As a Main Tool For Developing Sustaimentioning
confidence: 99%